Determinantes e implicações da estrutura de capital, da estrutura de propriedade e da governança corporativa: um modelo multiteórico de análise - Prado, José Willer do (2019)
At the present development stage of the modern Corporate Finance, one of the important topics of debate has been the possible costs and benefits of the separation of ownership and control. The separation caused a strong impact on both the Capital Structure and Ownership Structure. In this scenario, a corporate governance system comes into existence with the objective of offering an efficient alternative to solve the agency problems and other market imperfections originating from that separation. Different theories and hypotheses have arisen to understand these issues, and much of the current debate lies on methodological matters. For example, how various theories and their complex relationships can be tested simultaneously in a multitheoretical model of analysis and how accurate is such testing. Within this context, we seek to develop a multitheoretical model of analysis based on the relationships between Capital Structure, Ownership Structure, and Corporate Governance, from the perspective of market imperfections. The data collection was performed in two moments, both trough secondary sources. The first one was the bibliographical research on Web of Science and Scopus databases, in which bibliometric analyses were carried out. The second one was the documentary research on the quarterly/annual financial statements and Structured Reports, available in the Economática® database, on the website of the Securities and Exchange Commission of Brazil and on the B3 (Brazil, Bolsa, Balcão) website. The sample consisted of 241 companies listed in the B3, from 2013 to 2018. The empirical data analysis was done through the Partial Least Squares Structural Equation Modeling (PLS-SEM). Among the main findings it can be highlighted that, regarding Capital Structure determinants, the Pecking Order Theory was the most adapted to the sample. Regarding Ownership Structure determinants, most of tested hypotheses were accepted. The indirect effects revealed that Ownership Structure and Capital Structure have signs (indirect effects) opposite to Corporate Governance for mediation with market value. This may be explained by the fact that Corporate Finance seeks to correct imperfections, mostly originated in those two types of structure, such as: information asymmetry, agency conflicts, and bankruptcy costs. The ‘ownership concentration’ and the ‘identity of major shareholder’ in relation to Corporate Governance and Market Value were also tested. Regarding the identity of major shareholder, it was verified that family companies have opposite signs for Corporate Governance and Market Value. The findings also evidence that the multitheoretical model of analysis enables to apply an empirical approach comparing the three topics (Capital Structure, Ownership Structure, and Corporate Governance) and their respective theories. Finally, the findings indicate that good Corporate Governance practices are efficient in mitigating the impacts generated by the separation of ownership and control, both on the Capital and Ownership structures.